Altered Gene Expression Related to Glomerulogenesis and Podocyte Structure in Early Diabetic Nephropathy of db/db Mice and Its Restoration by Pioglitazone - Makino, Hisashi; Miyamoto, Yoshihiro; Sawai, Kazutomo; Mori, Kiyoshi; Mukoyama, Masashi; Nakao, Kazuwa; Yoshimasa, Yasunao; Suga, Shin-ichi (Diabetes (New York, N.Y.), 2006)
Altered Gene Expression Related to Glomerulogenesis and Podocyte Structure in Early Diabetic Nephropathy of db/db Mice and Its Restoration by Pioglitazone Hisashi Makino 1 , Yoshihiro Miyamoto 1 , Kazutomo Sawai 2 , Kiyoshi Mori 2 , Masashi Mukoyama 2 , Kazuwa Nakao 2 , Yasunao Yoshimasa 1 and Shin-ichi Suga 3 1 Department of Atherosclerosis and Diabetes, National Cardiovascular Center, Suita City, Osaka, Japan 2 Department of Endocrinology and Metabolism, Kyoto University Graduate School of Medicine, Kyoto, Japan 3 National Cardiovascular Center Research Institute, Suita City, Osaka, Japan Address correspondence and reprint requests to Shin-ichi Suga, MD, PhD, National Cardiovascular Center Research Institute, 5-7-1 Fujishiro-dai, Suita City, Osaka 565-8565, Japan. E-mail: s-sugaatumin.ac.jp Abstract Glomerular injury plays a pivotal role in the development of diabetic nephropathy. To elucidate molecular mechanisms underlying diabetic glomerulopathy, we compared glomerular gene expression profiles of db/db mice with those of db/m control mice at a normoalbuminuric stage characterized by hyperglycemia and at an early stage of diabetic nephropathy with elevated albuminuria, using cDNA microarray. In db/db mice at the normoalbuminuric stage, hypoxia-inducible factor-1α (HIF-1α), ephrin B2, glomerular epithelial protein 1, and Pod-1, which play key roles in glomerulogenesis, were already upregulated in parallel with an alteration of genes related to glucose metabolism, lipid metabolism, and oxidative stress. Podocyte structure-related genes, actinin 4α and dystroglycan 1 (DG1), were also significantly upregulated at an early stage. The alteration in the expression of these genes was confirmed by quantitative RT-PCR. Through pioglitazone treatment, gene expression of ephrin B2, Pod-1, actinin 4α, and DG1, as well as that of oxidative stress and lipid metabolism, was restored concomitant with attenuation of albuminuria. In addition, HIF-1α protein expression was partially attenuated by pioglitazone. These results suggest that not only metabolic alteration and oxidative stress, but also the alteration of gene expression related to glomerulogenesis and podocyte structure, may be involved in the pathogenesis of early diabetic glomerulopathy in type 2 diabetes. DG1, dystroglycan 1 GLEPP1, glomerular epithelial protein 1 HIF-1α, hypoxia-inducible factor-1α VEGF, vascular endothelial growth factor Footnotes The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked “advertisement” in accordance with 18 U.S.C. Section 1734 solely to indicate this fact. Accepted June 27, 2006. Received December 27, 2005. DIABETES